(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Ozone (O3) have many adverse impacts toward the living human, environment and O3 formed through the photochemical reaction with the aid of sunlight. Therefore, this study focused on the determination of O3, nitric oxide (NO), nitrogen dioxide (NO2) concentrations and meteorological parameters (temperature, humidity, wind speed and wind direction) three residential area namely Taman Tun Dr Ismail Jaya, Selangor as the urban area, Taman Delima, Sungai Petani, Kedah as the sub urban area and Taman Kifayah, Jeli, Kelantan as the rural area. The monitoring were continuously done for three days in 24 hours from 12 a.m. until 12 a.m. per day at each site. Aeroqual S500 series and weather station model RK900-01 were used to measure O3, NO, NO2 concentrations and meteorological parameters. The concentration of O3, NO, NO2 and the meteorological parameters were determined and O3 concentration was compared by one-way analysis of variance (ANOVA). Among the studied areas, the highest mean O3 concentration was recorded in Taman Delima, Sungai Petani with 35.2 ppb followed by Tun Dr Ismail Jaya with 33.3 ppb. Result suggested that sub urban areas showed higher mean O3 concentration compared to urban area which might linked to the availability of the O3 precursors in the area. As expected, the lowest mean O3 concentration recorded at Taman Kifayah, Jeli with 12.1 ppb as the area have limited O3 precursor’s sources. However, the ozone concentration at three residential areas were still under permissible level according to Recommended Malaysia Ambient Air Quality Guidelines (RMAAQ).